Qualitative research in counselling and psychotherapy - McLeod, John. (London : SAGE, 2001)
Takes the reader through each stage of the research process, explaining techniques for gathering data, writing up the study and evaluating the findings. This book describes each qualitative method and assesses it in terms of its own strengths and weaknesses.
Includes bibliographical references and index.
Keywords: Counseling -- Research. -- Methodology; Psychotherapy. -- Research -- Methodology; Psychotherapy -- methods